Mussels meatballs development strategy as an effort to improve the economy of the Kedungrejo village communities subdistrict Muncar - Tita Divya Carolin; Asfarina Hidayah (Journal of Aquaculture Science, 2021)
Kedungrejo Village is one of the villages located in Muncar District, Banyuwangi. This village is known as the largest marine fish producer in East Java since 2010. This is because the area is very close to the sea coast so that the majority of the population there are fishermen. This village area is famous as an industrial center related to marine products, such as the fish canning industry, animal feed production industry, and so on. One of the marine catches from fishermen in Kedungrejo Village is sea shells. One way to support economic growth in Kedungrejo Village is to maximize the potential of the village which is famous for its marine sector. The purpose of this research is to support the economy of Kedungrejo Village by developing MSMEs related to marine products. The research method used is data collection techniques and descriptive SWOT analysis method. From this research, it produces a Baskerang (Scallop Meatball) product which has a very large opportunity because it is not widely known by many circles.  Keyword : clam meatballs, economic improvement, Muncar